FACTORS AND DIFFERENCES OF STANDPOINTS BETWEEN MAINSTREAM AND TRIBUTARY RESIDENTS OF MANTAYUPAN ON WATER QUALITY MANAGEMENT - Pascual, Valerie U (Journal of Agriculture and Technology Management, 2022)
Mantayupan River in the Municipality of Barili is the major source of water for various purposes. The river was indicated medium quality, but the increasing settlements along its bank may eventually render it unfit for its purpose. Community-based programs have been proven effective since it instills ownership among community members. The study evaluates socio-demographic characteristics, media exposure and information seeking behavior as determinants of the households’ standpoint in terms of knowledge, attitude and practice towards water quality management of the Mantayupan River. Villages were grouped into tributaries and mainstream using a simple random sampling. This was applied for the respondents to comprise 30% of the population at 10% margin of error. For both mainstream and tributary; female, high school graduates, native of Barili, residing 35 years and above and income below Php 15,780 per month comprised the highest percentage of respondents. For mainstream respondents, years of residence, household income, television and print media exposure positively influenced their standpoints for a community- based water management system. For tributary respondents, radio media exposure significantly was found to positive influence standpoint. Considering that radio listenership positively affects standpoints of tributary residents, “Radyo Kahimsug” of Cebu Technology University –Barili Campus will therefore have a significant role to play. Upon comparison, mainstream respondents have significantly better attitude toward water management.